Near Real-Time Estimation of Super-Resolved Depth and All-In-Focus Images from a Plenoptic Camera Using Graphics Processing Units - J. P. Lüke; F. Pérez Nava; J. G. Marichal-Hernández; J. M. Rodríguez-Ramos; F. Rosa (International Journal of Digital Multimedia Broadcasting)
Depth range cameras are a promising solution for the 3DTV production chain. The generation of color images with their accompanying depth value simplifies the transmission bandwidth problem in 3DTV and yields a direct input for autostereoscopic displays. Recent developments in plenoptic video-cameras make it possible to introduce 3D cameras that operate similarly to traditional cameras. The use of plenoptic cameras for 3DTV has some benefits with respect to 3D capture systems based on dual stereo cameras since there is no need for geometric and color calibration or frame synchronization. This paper presents a method for simultaneously recovering depth and all-in-focus images from a plenoptic camera in near real time using graphics processing units (GPUs). Previous methods for 3D reconstruction using plenoptic images suffered from the drawback of low spatial resolution. A method that overcomes this deficiency is developed on parallel hardware to obtain near real-time 3D reconstruction with a final spatial resolution of 800×600 pixels. This resolution is suitable as an input to some autostereoscopic displays currently on the market and shows that real-time 3DTV based on plenoptic video-cameras is technologically feasible.